The Instructional Design Of The Teaching English As Foreign Language At Kindergartens In Salatiga: Micro Ethnography - Sulaikah, Siti, Prof. Dr. Endang Fauziati, M. Hum, Drs. Abdillah Nugroho, M. Hum (2013)
The objective of the study is to describe briefly the instructional design of teaching English at three Kindergartens in Salatiga, namely Kartika III-39, Aisiyah Pembina and Aisiyah 3. The Instructional design includes syllabus, learning objective, teaching method, teaching procedure, instructional material, teaching media, evaluation ,teacher and student's role, strength and weaknesses.The research was conducted in micro ethnographic. The syllabus used is the combination of functional- notional and topic or content - syllabus .Another meaning of learning objective is indicator or aim. The instructional material is only printed material where picture is dominant. Teacher's roles are as guide, helper, model, facilitator, and story teller. The student's roles are protagonist, constructor, and collaborator. The classroom procedures used patterns namely PPP (Presentation, Practice, and Produce) or ESA (Engage, Study, and Active), ARC (Authentic, Restricted, Clarification). The classroom activities are singing, game and story. The media is printed media. The evaluation is in the form of student's observation, portfolio, and rubric. Based on the finding, discussion, conclusion and implication, the writer suggests for English teacher to complete visual and audio media that emphasized the use of flash card or animation so the teaching will be more fun. Teaching English for Kindergarten students are not only merely used gesture or command from the teacher but the variation of method, technique is obviously needed in English teaching.